Effectivity Of Coffee Mistletoe Extract (Loranthus ferrugineus Jack) As Insecticide Against Culex sp. - Rosi Esa Gustina; Serli Seprinanda (CV. Inara, 2022)
Coffee mistletoe (Loranthus ferrugineus Jack) contains phytochemical compounds such as alkaloid, flavonoid, saponin and tannin. The compounds possess natural insecticide properties against mosquito larva. The aim of this study was to obtain the effectivity of coffee mistletoe extract as larvicidal agent against Culex sp. The study was designed as a post test only control group with a total of 80 tested larvae and 24 hr of observation. The concentration of administered extract was 0% (K0), 0.7% (P1), 0.9 % (P2) and 2% (P3). Based on ANOVA test, there was a significant difference between control group and treatment group (p=0.001<α(0.05)). Based on a post hoc analysis result, the larvicidal percentage was significant between K0 and P2 (p=0.013), K0 and P3 (p=0.001), P1 and P2 (p=0.045), P1 and P3 (p=0.002), and between P2 and P3 (p=0.023). In this case, there was no significant difference between K0 and P1 group (p=0.697). The coffee mistletoe extracts were then proved to exhibit larvicidal activities against Culex sp. larva.